2019
DOI: 10.1523/jneurosci.1443-17.2019
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of GpI mGluR-Dependent Cav2.3 Translation in a Mouse Model of Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is an inherited intellectual impairment that results from the loss of fragile X mental retardation protein (FMRP), an mRNA binding protein that regulates mRNA translation at synapses. The absence of FMRP leads to neuronal and circuit-level hyperexcitability that is thought to arise from the aberrant expression and activity of voltage-gated ion channels, although the identification and characterization of these ion channels have been limited. Here, we show that FMRP binds the mRNA of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Nifedipine can block Cav1.2 current [ 146 ] Oxidative stress pathway for affective disorders [ 156 ] Apoptotic pathway in Timothy syndrome [ 153 ] Apoptotic pathway in dilated cardiomyopathy [ 154 ] CACNA1D Calcium voltage-gated channel subunit alpha1 D Cav1.3 L-type None Zebrafish larvae for schizophrenia [ 251 ]. Animal model of epilepsy [ 252 ] None Oxidative stress pathway in hearing loss [ 157 ] CACNA1E Calcium voltage-gated channel subunit alpha1 E Cav2.3 R-type Mouse model of Fragile X Syndrome [ 253 ] Sprague–Dawley rats for epilepsy [ 254 ]. Cancer pain mouse model [ 255 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nifedipine can block Cav1.2 current [ 146 ] Oxidative stress pathway for affective disorders [ 156 ] Apoptotic pathway in Timothy syndrome [ 153 ] Apoptotic pathway in dilated cardiomyopathy [ 154 ] CACNA1D Calcium voltage-gated channel subunit alpha1 D Cav1.3 L-type None Zebrafish larvae for schizophrenia [ 251 ]. Animal model of epilepsy [ 252 ] None Oxidative stress pathway in hearing loss [ 157 ] CACNA1E Calcium voltage-gated channel subunit alpha1 E Cav2.3 R-type Mouse model of Fragile X Syndrome [ 253 ] Sprague–Dawley rats for epilepsy [ 254 ]. Cancer pain mouse model [ 255 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recordings of isolated dendritic Ca 2+ spikes suggest that CA1 dendritic voltage-gated Ca 2+ channels are not different between wild type and fmr1 KO neurons. Previous studies have shown that changes in voltage-gated Ca 2+ channels in fmr1 KO mice occur in a brain region and cell type specific manner [33][34][35] . Our results further illustrate that changes in ion channel function and expression in FXS are not conserved across brain regions.…”
Section: Dendritic Nonlinear Events In Fmr1 Ko Ca1 Neuronsmentioning
confidence: 98%
“…The mechanistic aspects of the connection between synaptic NMDARs and R‐VGCCs will warrant further investigation. Potential involvement of translational regulation (Figure 1h) is especially relevant in the light of the recent studies showing the link between postsynaptic mGluR activation and R‐VGCC translation (Gray et al., 2019; Park et al., 2010), given the primarily postsynaptic localization of NMDARs (Paoletti et al., 2013). Also, recent findings have demonstrated considerable abundance of Ca V 2.3 mRNA in the presynaptic compartment compared to other Ca V 2‐containing VGCCs (Hafner et al., 2019), suggesting that Ca V 2.3 translation may also occur at the presynaptic site.…”
Section: Resultsmentioning
confidence: 98%